Determination Of The Effect Of Ph On Microalagal Growth And Protein Content In Locally Isolated Tetraselmis Suecica And Scenedesmus Parvus - Yeong, Kah Chuen (Universiti Sains Malaysia, 2020)
Mass production of certain protein rich microalgae as single cell protein was considered as a possibility to minimise the protein gap due to increasing of global population. However, the protein productivity and the growth of the microalgae will be affected by the cultivation condition during the mass production. Thus, this project is to explore the possibility of the locally isolated microalgae as a single cell protein source where both microalgae Tetraselmis suecica and Scenedesmus parvus were cultivated in different initial pH cultivation medium (pH 3.00 to pH 9.00).